PLASMALEMMA POTENTIAL IN NITELLA - KISHIMOTO, UICHIRO; NAGAI, REIKO; TAZAWA, MASASHI (Oxford University Press, 1965)
A considerable part of the response of the vacuolar potential of Nitella flexilis to the change of external KCl, NaCl, RbCl, LiCl, or CaCl 2 concentration is caused by the response of the cell wall (a cation exchanger) to the external medium. The potentials were measured on the internodes whose cell sap was exchanged for simple salt solutions. The potential difference across the plasmalemma which is the internal potential measured against the cell wall phase changes largely with the change in concentration of the external KCl, but also more or less with that of the external NaCl, LiCl or RbCl. CaCl 2 depolarizes the plasmalemma potential by about 50 mv when the concentration is increased from 10−5 M to 10−3 M, and hyperpolarizes it again by about 40 mv from 10−3 M to 10−1 M leaving the level of the peak of the action potential almost unchanged.